Implementation of patient safety strategies in European hospitals. (2nd February 2009) - Suñol, R; Vallejo, P; Groene, O; Escaramis, G; Thompson, A; Kutryba, B; Garel, P
Abstract : Context: This study is part of the Methods of Assessing Response to Quality Improvement Strategies (MARQuIS) research project on cross-border care, investigating quality improvement strategies in healthcare systems across the European Union (EU). Aim: To explore to what extent a sample of acute care European hospitals have implemented patient safety strategies and mechanisms and whether the implementation is related to the type of hospital. Methods: Data were collected on patient safety structures and mechanisms in 389 acute care hospitals in eight EU countries using a web-based questionnaire. Subsequently, an on-site audit was carried out by independent surveyors in 89 of these hospitals to assess patient safety outputs. This paper presents univariate and bivariate statistics on the implementation and explores the associations between implementation of patient safety strategies and hospital type using the χ 2 test and Fisher exact test. Results: Structures and plans for safety (including responsibilities regarding patient safety management) are well developed in most of the hospitals that participated in this study. The study found greater variation regarding the implementation of mechanisms or activities to promote patient safety, such as electronic drug prescription systems, guidelines for prevention of wrong patient, wrong site and wrong surgical procedure, and adverse events reporting systems. In the sample of hospitals that underwent audit, a considerable proportion do not comply with basic patient safety strategies—for example, using bracelets for adult patient identification and correct labelling of medication.